Comprehensive evaluation of dopant solubility, proton concentration, proton mobility and phase stability of lanthanum polyphosphate for conductivity improvement. (14th December 2016) - Adachi, Yoshinobu; Hatada, Naoyuki; Uda, Tetsuya
Abstract: Lanthanum polyphosphate (LaP3 O9 ) is a candidate for the electrolytes in protonic ceramic fuel cells (PCFCs). In this work, the solubility of dopants (Ca, Sr, Ba and Pb), proton concentration, and proton mobility in LaP3 O9 were evaluated to clarify the limiting factors for conductivity improvement. The maximum doping levels of Ca, Sr, Ba, and Pb in LaP3 O9 synthesized by precipitation method were about 8, 14, 3, and 6 mol% respectively. Here doping level is defined as the concentration ratio of the dopant (M) to the host cation (La) site (M/(La + M)). The concentration ratio of protons to the dopant cations in doped LaP3 O9, or hydration level, was almost independent of dopant species and as high as those in the perovskite-type oxides. The proton mobility in Sr-doped LaP3 O9 was about twice those of Ca and Ba-doped LaP3 O9, and it was ∼7 times that of Pb-doped LaP3 O9 . Remarkably, the highest conductivity of Sr-doped LaP3 O9 precipitated from phosphoric acid solution was about one order of magnitude higher than that synthesized by solid state reaction, and comparable to that of Sr(Zr0.9 Y0.1 )O3-δ . This conductivity enhancement should be attributed to the increase in Sr-doping level, reduction of grain boundary density and c-axis orientation of grains by the precipitation method. Nevertheless, instability of LaP3 O9 in humidified hydrogen atmosphere should be a problem for the practical applications. Highlights: Precipitation method enhanced Sr-doping level by 5 times than solid state reaction. Hydration level (or proton/dopant ratio) was almost independent of dopant species. Proton mobility was heavily dependent on dopant species. Conductivity of precipitated Sr-doped LaP3 O9 were comparable to SrZr0.9 Y0.1 O3 .